BERPIKIR DALAM PERSPEKTIF ALQURAN - Malkan, Malkan (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article deals with Ø§Ù„ØªÙÙƒØ± in the Qurâ€™an employing the thematic method of qurâ€™anic exegesis. Observing the verses used the Qurâ€™an, the writer found some words in the Qurâ€™an denoting both negative and positive thinking. To denote the negative thinking, the word ØªØªÙÙƒØ±ÙˆÙ† is used; to denote the things related to the prohibition of drinking liquor and of gambling; the word ØªØ¹Ù‚Ù„ÙˆÙ† is used; to denote the order to do good things; the word Ù†Ø¸Ø± is used; to denote al-Walid al-Mughirahâ€™s negation to the Qurâ€™an; to denote the unbelieversâ€™ accuses of the prophet Muhammad, the word Ø§ØÙ„Ø§Ù… is used. In the mean time, to denote the positive thinking, the Qurâ€™an adopts the word ÙŠØªÙÙƒØ±ÙˆÙ†Â that is something related to the creature of the universe and of the natural phenomena; the word ÙŠÙ†Ø¸Ø± is used to denote the origin of human beings; the word Ø§ÙˆÙ„Ùˆ Ø§Ù„Ø§Ù„Ø¨Ø§Ø¨ is used to denote agreement and negation to truth of the Qurâ€™an.Â Kata Kunci: tafsir, berpikir, Alquran